An Assessment of Knowledge Sharing Among Academics in Bayero University, Kano, Kano State, Nigeria - Kabiru , Dahiru Abbas (MiddleBelt Journal of Library and Information Science, 2020)
The paper aims to investigate the phenomenon of knowledge sharing among academic staff in Bayero University, Kano, Nigeria using quantitative approach through questionnaire, administered randomly on one hundred and twenty (120) academic to collect data for the study. The study found the evidence of knowledge sharing among academics in the university through workshops, seminars and conferences, membership of professional associations/societies and postgraduate thesis supervision. The findings further show that phone (both landline and mobile), instant messaging/chat, LinkedIn and face-to-face interaction were the means of communication among academics. The study serves as a source of encouragement for the Universities and their lecturers in Nigeria to re-evaluate and re-strategise the present scenario, particularly regarding use of sophisticated technologies to increase awareness, communication and networking for improved research and teaching activities. Knowledge sharing as critical factor in the survival of educational institutions across the globe, Bayero University, Kano academics, in particular and academics all over the country, are encouraged to foster collaborations and synergies in order to boost scholarship and knowledge production. The main contribution of this paper is that it investigated the knowledge sharing activities in Bayero University, Kano, thereby created awareness on the for collaboration and communication among academics.